Expression of milk-derived angiotensin I-converting enzyme-inhibitory peptides in Lactococcus lactis. Issue 2 (3rd April 2019) - Zhuang, Kejin; Jiang, Yujun; Li, Mingyu; Li, Hongfu; Feng, Xiaohan; Qu, Xingguang; Man, Chaoxin
ABSTRACT: Angiotensin I-converting enzyme (ACE) plays a key role in the regulation of blood pressure. Currently, most single or tandem repeats of ACE-inhibitory (ACE-I) peptides have been expressed in Escherichia coli . However, in this study, a food-grade system was constructed using Lactococcus lactis ( L. lactis ) to simultaneously express four different milk-derived ACE-I peptides with antihypertensive activity. Mixed peptides (MPs) fused with green fluorescent protein (GFP) and eight histidines were synthesized. To ensure potent ACE inhibition by the MPs in human digestive juice, pepsin and trypsin cleavage sites were introduced among the four ACE-I peptides. The MP fusion gene was inserted into expression vector pSEC-E7 with nisin induction and expressed in L. lactis NZ9000, then purified by affinity chromatography. The transformants containing pSEC-MP:GFP were identified based on green fluorescence using Leica laser scanning confocal microscopy. The target proteins were detected by SDS-PAGE analysis and displayed obvious immunogenicity by western blot. After hydrolysis with digestive enzymes, the IC50 of the MPs was 118.63 μM. These results suggested that multiple milk-derived ACE-I peptides with antihypertensive properties could be produced using a food-grade lactococcal expression system.